“Turn-On” Fluorescent Biosensors for High Selective and Sensitive Detection of Al3+ Ion - Wang, Pengfei; Liu, Lijie; Meng, Fanda; Khan, Maroof Ahmad; Li, Hui (Frontiers in Chemistry, 2020)
A series of new compounds(1-4) based on Pyrole Hydrazone Shiff Bases were designed and synthesized. The interactions of these new compounds with metal ions and fluorescent recognition of them have been investigated. All compounds showed ‘turn-on’ fluorescence in the presence of Al3+ in aqueous solution. Their sensing behaviors with Al3+ were studied by using photophysical experiments, ESI-MS spectrometry analysis, 1H NMR titration and DFT calculation. The detection limits of 1-4 for the analysis of Al3+ were found to reach at 10-8 M level in aqueous solution, which are far lower than the WHO guidelines for drinking water (7.41 mM for Al3+). A high selectivity test paper has been fabricated for Al3+ detection based on sensor 3. Theoretical calculations (DFT) have been carried out to elucidate the configuration of 1-4 and their Al complexes and rationalize experimental absorption data.